Impact of renal impairment on early development of severe neutropenia with trifluridine/tipiracil treatment for metastatic colorectal cancer - Yoshitaka Saito; Yoh Takekuma; Yoshito Komatsu; Mitsuru Sugawara (Scientific Reports)
Abstract Trifluridine/tipiracil (FTD/TPI) with or without bevacizumab is an effective treatment for metastatic colorectal cancer (mCRC). As this agent is mainly excreted via the kidney, we aimed to evaluate the impact of renal impairment (RI) on the early development of severe neutropenia, a dose-limiting toxicity and whose development reflects better treatment outcomes, in patients with mCRC treated with FTD/TPI. Patients with mCRC receiving FTD/TPI ± bevacizumab (n = 100) were divided into the RI group (creatinine clearance [CCr] < 90 mL/min) or control group (CCr ≥ 90 mL/min), and retrospectively evaluated. Severe neutropenia during the first two cycles occurred in 57.6% and 34.2% of patients in the RI and control groups, respectively, which was significantly different (P = 0.03) and met our primary endpoint. Furthermore, the incidence during the first cycle also differed significantly (52.5% in the RI group and 17.1% in the control group, P = 0.0004). Multivariate logistic regression analysis suggested that baseline RI and neutropenia were significant risk factors for early severe neutropenia (adjusted odds ratio and 95% confidence interval: 3.07, 1.24–7.59, P = 0.02 for RI, and 9.76, 1.08–88.11, P = 0.04 for neutropenia). In conclusion, our study suggested that patients with RI can exhibit early severe neutropenia during real-world FTD/TPI treatment for mCRC.